2007
DOI: 10.1203/pdr.0b013e3180987202
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Connective Tissue Growth Factor in Hyperoxia-Induced Lung Fibrosis

Abstract: Pulmonary oxygen toxicity plays an important role in the lung injury process that leads to the development of bronchopulmonary dysplasia. Connective tissue growth factor (CTGF) is a fibroblast mitogen and promoter of collagen deposition. We investigated the effects of postnatal hyperoxia on lung collagen and CTGF expression in rats. Rat pups were exposed to 7 d of Ͼ95% O 2 and a further 3 wk of 60% O 2 . CTGF mRNA and protein expression increased after hyperoxia treatment, and the values were significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 31 publications
8
55
1
Order By: Relevance
“…Prolonged exposure of neonatal rats to hyperoxic conditions has been reported to increase lung fibrosis in a manner similar to that observed for human BPD (3,4). Collagen is the major extracellular matrix component of the lungs and is vital for maintaining the normal lung architecture (28).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Prolonged exposure of neonatal rats to hyperoxic conditions has been reported to increase lung fibrosis in a manner similar to that observed for human BPD (3,4). Collagen is the major extracellular matrix component of the lungs and is vital for maintaining the normal lung architecture (28).…”
Section: Discussionmentioning
confidence: 71%
“…Lung injury resolves with fibrosis that is prominent in larger infants who developed bronchopulmonary dysplasia (BPD) after prolonged exposure to oxygen and mechanical ventilation (1,2). Prolonged exposure of neonatal mice to hyperoxic conditions resulted in decreased alveolar septation, increased terminal air space size, and increased lung fibrosis that is similar to human BPD (3,4).…”
mentioning
confidence: 99%
“…Previous studies have shown that hyperoxia induces fibrotic gene expression such as that of CTGF (30). Furthermore, anti-CTGF therapy attenuates hyperoxia-induced alveolar damage and vascular remodeling (31).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical association of CTGF with BPD is best established by studies demonstrating increased CTGF concentrations in bronchoalveolar lavage fluid from preterm infants developing BPD (5) and increased CTGF expression in lung tissues of infants who died of BPD (6). Multiple studies have examined the potential role of CTGF in experimental BPD and demonstrated that increased CTGF expression is associated with chronic hyperoxia as well as mechanical ventilationinduced lung injury in neonatal rodents (6)(7)(8)(9)(10). Recent studies from our laboratory utilizing genetic gain-of-function and biological loss-of-function approaches have provided compelling evidence that a novel signaling network orchestrated by CTGF plays an important role in BPD pathogenesis (6,11,12).…”
Section: Introductionmentioning
confidence: 99%